An Entry to Mixed NHC–Fischer Carbene Complexes and Zwitterionic Group 6 Metal Alkenyls. Issue 38 (26th July 2016) - Sierra, Miguel A.; Merinero, Alba D.; Giner, Elena A.; Gómez‐Gallego, Mar; Ramírez de Arellano, Carmen
Abstract: The addition of NHCs to α, β‐unsaturated Cr 0 and W 0 (Fischer) carbene complexes is strongly dependent on the electrophilicity of the carbene carbon. Electrophilic alkoxy–carbene complexes quantitatively react with NHCs to yield stable zwitterionic (racemic) Cr 0 ‐ and W 0 ‐alkenyls with total regio‐ and E ‐stereoselectivity. Less electrophilic aminocarbenes react with NHCs to promote the displacement of a CO ligand and yield "mixed" NHC/Fischer biscarbenes in a process that is unprecedented in group 6 metal–carbene chemistry. In fact, the compounds prepared, are some of the scarce examples of Fischer bisylidenes reported in the literature. The electrochemistry of the zwitterionic Cr 0 ‐ and W 0 ‐alkenylcomplexes made, show that these compounds have a strong reductor character, which is demonstrated in their reactions towards [Ph3 C][PF6 ]. The oxidation processes lead to new types of cationic Fischer mono‐ and biscarbene complexes having a charged NHC fragment in their structures, in a new example of the use of electron‐transfer reactions as a method to prepare novel group 6 (Fischer) carbene complexes. Abstract : The heteroatom makes the difference : The addition of NHCs to α, β‐unsaturated Cr 0 and W 0 (Fischer) carbene complexes depends on the electrophilicity of the carbene carbon. Alkoxy–carbene complexes react with NHCs in quantitative yields to form stable zwitterionic (racemic) Cr 0 ‐ and W 0 ‐alkenyls, while NHCs promote the displacement of a CO ligand in less electrophilic amino carbenes to yield "mixed" NHC/Fischer biscarbenes (see scheme) in a process unprecedented in group 6 metal–carbene chemistry.